2021
DOI: 10.3389/fimmu.2020.586796
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis and Immunotherapeutics Based on Human Papillomavirus for HPV-Induced Cancers

Abstract: Infection with human papillomavirus (HPV) is one of the main causes of malignant neoplasms, especially cervical, anogenital, and oropharyngeal cancers. Although we have developed preventive vaccines that can protect from HPV infection, there are still many new cases of HPV-related cancers worldwide. Early diagnosis and therapy are therefore important for the treatment of these diseases. As HPVs are the major contributors to these cancers, it is reasonable to develop reagents, kits, or devices to detect and eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 157 publications
(186 reference statements)
0
24
0
1
Order By: Relevance
“…HPV is a small non-enveloped, circular, double-stranded DNA virus with epithelial tropism and commonly transmits by sexual contact. It has been reported that HPV infection was attributed to around 20% ~ 60% of OPSCC worldwide ( 9 , 21 ). Among 200 identified genotypes of HPVs, genotype HPV-16 accounts for over 80% of HPV-positive OPSCC, followed by HPV-18, 31, 33, 35, which are well-known high-risk HPVs ( 9 , 22 ).…”
Section: Hpv and Opsccmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is a small non-enveloped, circular, double-stranded DNA virus with epithelial tropism and commonly transmits by sexual contact. It has been reported that HPV infection was attributed to around 20% ~ 60% of OPSCC worldwide ( 9 , 21 ). Among 200 identified genotypes of HPVs, genotype HPV-16 accounts for over 80% of HPV-positive OPSCC, followed by HPV-18, 31, 33, 35, which are well-known high-risk HPVs ( 9 , 22 ).…”
Section: Hpv and Opsccmentioning
confidence: 99%
“…E6 and E7, two early viral proteins expressed by high-risk HPV, are mainly involved in developing and maintaining the transformed phenotype of HPV-induced cancers ( 23 ). Specifically, the oncoprotein E6 degrades the tumor suppressor p53 and helps escape cell death ( 21 , 24 ). E7 binds to the retinoblastoma proteins (pRb), promoting the E2F/pRb complex dissociation and releasing E2F, which stimulates the cell re-entering S-phase, leading to escape from oncogene-induce senescence ( 21 , 25 ).…”
Section: Hpv and Opsccmentioning
confidence: 99%
“…The HPV genome is represented by a small double-stranded and highly conserved DNA with a molecular weight of 5 × 10 6 Daltons and contains approximately 7906 base pairs, including two coding regions (E and L) and one non-coding region called the long control region or upstream regulatory region (URR) (Figure 3) [15,16]. The E region encodes six early proteins (E1, E2, E4, E5, E6, and E7), three of them being regulatory proteins (E1, E2, and E4) and three of them being oncoproteins (E5, E6, and E7) that participate in the processes of replication and transformation of the host cells [17].…”
Section: Hpv: Structure Pathogenicity and Transformation Activitymentioning
confidence: 99%
“…E1 and E2 are specifically involved in transcription and replication, E4 is involved in the process of virion release, E5 modulates cell proliferation, and E6 and E7 control the principal signaling pathways in the host cell [18]. The L region encodes two late proteins (L1 and L2), which are the structural proteins that form the viral capsid; L1 is responsible for the major viral capsid and L2 is responsible for the minor viral capsid [15,17,18]. The long control region contains the viral open reading frame (ORF) and the promoter and enhancer elements that modulate the viral DNA replication and transcription [17,18].…”
Section: Hpv: Structure Pathogenicity and Transformation Activitymentioning
confidence: 99%
“…The main treatment methods for cervical cancer are surgery, radiotherapy and chemotherapy, and targeted therapy. Although cervical cancer screening and advanced medical methods have reduced the incidence of cervical cancer by 40-50% [3]. However, cervical cancer is still a major public health problem, and the prognosis of patients is poor, especially in advanced cases [4].…”
Section: Introductionmentioning
confidence: 99%